2015
DOI: 10.1007/s00253-015-6633-y
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community diversity in municipal waste landfill sites

Abstract: Little is known about the bacterial diversity of landfills and how environmental factors impact the diversity. In this study, PCR-based 454 pyrosequencing was used to investigate the bacterial communities of ten landfill leachate samples from five landfill sites in China. A total of 137 K useable sequences from the V3-V6 regions of the 16S rRNA gene were retrieved from 205 K reads. These sequences revealed the presence of a large number of operational taxonomic units (OTUs) in the landfills (709-1599 OTUs per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(65 citation statements)
references
References 52 publications
7
55
3
Order By: Relevance
“…The pH of leachate samples RL and FL2 were 7.78 and 8.12, respectively (Table 2). This range of pH has been reported in other landfill leachate studies conducted in China (Song et al, 2015a, D r a f t Song et al, 2015b, Li et al, 2014. Since this landfill has an onsite incinerator, the alkaline pH could be attributed to the disposal of ash in the landfill.…”
Section: Comparison Of Ph and Heavy Metals Between Sitessupporting
confidence: 77%
See 3 more Smart Citations
“…The pH of leachate samples RL and FL2 were 7.78 and 8.12, respectively (Table 2). This range of pH has been reported in other landfill leachate studies conducted in China (Song et al, 2015a, D r a f t Song et al, 2015b, Li et al, 2014. Since this landfill has an onsite incinerator, the alkaline pH could be attributed to the disposal of ash in the landfill.…”
Section: Comparison Of Ph and Heavy Metals Between Sitessupporting
confidence: 77%
“…Leachate samples RL and FL2 had the least diverse phyla detection, in contrast to other landfill leachate studies (Song et al, 2015a, Wang et al, 2017. The high concentration of As and Hg in RL and FL2 could have inhibited the growth of other phyla, whereas Pseudomonas spp.…”
Section: Dominant Phyla and Genera In Both Sitesmentioning
confidence: 69%
See 2 more Smart Citations
“…23,45,48 An adequate equilibrium between syntrophic bacteria and methanogens promotes CH 4 production because this relationship is essential to maintain nontoxic concentrations of VFAs and H 2 that affect both microbial groups. 50 Desulfomicrobium and Desulfovibrio are sulfate-reducing bacteria that play an important role in organic matter recycling and produce H 2 S. 36 Rhizobium, Luteimonas and Rhodococcus are usually found in landfills and contribute to the removal of toxic waste products such as aromatic compounds, promoting CH 4 production. 45,51 In addition, a methanotroph of the genus Methylocaldum and pathogens such as Mycobacterium and wileyonlinelibrary.com/jctb Nocardia were found that have not been reported to be involved in anaerobic digestion.…”
Section: Bacterial and Methanogen Community At The Genus Levelmentioning
confidence: 99%